Effect of sand and crosswind on the performance of solar chimney power plant - Lu Zuo; Pengzhan Dai; Huimin Yan; Ling Zhou (Energy Science & Engineering, 2023)
Abstract A solar chimney power plant (SCPP) is suitable to be deployed in desert areas, but there are few studies on the impact of desert wind and sand. In this paper, numerical simulations for the Spanish prototype SCPP were conducted to investigate desert environmental parameters, including sand movement, crosswind, and sand deposition, on the output performance of SCPP. The results indicate that the main erosion area of the turbine blade in the SCPP is the leading edge of the blade pressure surface. The erosion area of the suction surface is much less than that of the pressure surface, mainly concentrated on the leading edge. The output power of SCPP is reduced by 73.3% because of the crosswind and it decreases by 16.9% after the windbreak wall is installed. The sand and dust deposition would affect the transmissivity of the solar radiation through the collector cover. In a dusty environment for 1 month, the system output power decreased by 12.9%, and the collector efficiency decreased from 34% to 23% due to the sand deposition. These results show that the sand has a considerable negative effect on the performance of SCPP in ways of sand erosion and deposition. Sand removal is necessary for SCPP.